MicroRNA molecules as predictive biomarkers of adaptive responses to strength training and physical inactivity in haemodialysis patients - Spakova, Ivana (Sci Rep, 2020)
The miRNA-206 and miRNA-23a play an important role in muscle tissue hypertrophy, regeneration and atrophy. Both of these miRNAs have been highlighted as promising adaptation predictors; however, the available evidence on associations is inconclusive. Therefore, our aim was to assess the expression levels of these two miRNAs as predictors of change in muscle function during strength training and physical inactivity among dialysed patients. For this purpose, 46 haemodialysis patients were monitored for 12-weeks of either intradialytic strength training (EXG, n = 20) or physical inactivity during dialysis (CON, n = 26). In both groups of patients, we assessed the baseline expression levels of miRNA-23a and miRNA-206 and the isometric force generated during hip flexion (HF) contraction before and after the 12-week period. Among the EXG group, the expression of miRNA-206 predicted the change in HF (R(2) = 0.63, p = 0.0005) much more strongly than the expression of miRNA-23a (R(2) = 0.21, p = 0.027). Interestingly, baseline miRNA-23a (R(2) = 0.30, p = 0.006) predicted the change in HF much more than miRNA-206 (p = ns) among the CON group. Our study indicates that the baseline expression of miRNA-206 could predict the response to strength training, while miRNA-23a could serve as a potential predictive marker of functional changes during physical inactivity in dialysis patients.